Emotional Intelligence in Education: A Systematic Literature Review of its Influence on Student Performance and Well-Being - Edwin; I Gde Wawan Sudatha; I Kadek Suartama; Made Hery Santosa (Jurnal Penelitian Pendidikan IPA, 2025)
This study addresses the limited comprehensive understanding of emotional intelligence (EI) in educational settings. It aims to systematically review literature on the relationship between EI, academic achievement, and student well-being. A systematic literature review was conducted using predefined criteria, incorporating 2020–2025 studies indexed in Google Scholar and analyzed using Harzing's Publish or Perish and VOSviewer. Meta-analysis results reveal a significant positive correlation between EI and both academic performance and psychological well-being. Students with high EI demonstrate greater emotional regulation, self-esteem, and resilience. Moreover, positive teacher-student relationships and supportive learning environments amplify these effects. Despite the findings, limitations such as reliance on self-report data and underexplored cultural factors persist. Future research should implement longitudinal and diverse methodological approaches to deepen the understanding of EI's impact on holistic student development.